2013
DOI: 10.1556/amicr.60.2013.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antibiotic combinations for colistin-resistantKlebsiella pneumoniae

Abstract: In this study antibiotic combinations for multidrug-resistant Klebsiella pneumoniae strains were investigated. The study included a colistin-susceptible and a colistin-resistant KPC-2 producing K. pneumoniae ST258 strains isolated in 2008 and 2009 during an outbreak in Hungary. Antibiotic combinations were analyzed by checkerboard technique and fractional inhibitory concentration indices were calculated. The following antibiotics were tested: ceftazidime, cefotaxime, ceftriaxone, ampicillin, imipenem, ertapene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…The treatment of these polymyxin-resistant enterobacteria is a great challenge, although some recent studies showed that antibiotic combinations involving e.g. polymyxins, rifampicin, carbapenems and aminoglycosides could be effi cient [29].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of these polymyxin-resistant enterobacteria is a great challenge, although some recent studies showed that antibiotic combinations involving e.g. polymyxins, rifampicin, carbapenems and aminoglycosides could be effi cient [29].…”
Section: Discussionmentioning
confidence: 99%
“…Microbroth plates When synergy was detected by CB, a time-kill assay (TKA) was performed at 1xMIC following a previously published method (8). When MICs were above the therapeutic level, SXT was used at 8 mg/L and colistin at 4 mg/L, which fits the peak serum levels of these agents (9). Twenty ml of SXT, colistin and SXT-plus-colistin containing MuellerHinton II broth were inoculated with bacteria to yield a density of 106 CFU/mL in the final volume.…”
Section: Methodsmentioning
confidence: 99%
“…Эффект потенцирования антибактериальной актив ности колистина антибиотиками, не способными в обыч ных условиях проникать через наружную мембрану грамотрицательных бактерий к внутриклеточным ми шеням, заслуживает более детального изучения в отно шении различных видов энтеробактерий и грамотрица тельных неферментирующих бактерий с множественной и экстремальной антибиотикорезис тентностью. В ряде работ показана способность колистина потенцировать активность АМП, действующих на внутриклеточные ми шени (рифампицина, триметоприма, гликопептидов и фторхинолонов) в отношении колистинорезистентных K. pneumoniae, A. baumannii и P. aeruginosa [15][16][17]. Ограничением указанных исследований являлось изу чение преимущественно лабораторных колистинорези стентных мутантов и реципиентов mcr1несущих плаз мид, а также небольшое количество исследованных колистинорезистентных клинических изолятов, что мо жет быть связано с тем, что они относительно низко представлены в бактериальных популяциях, а также со значительной трудоемкостью использованных ме тодов.…”
Section: Discussionunclassified